Assessment of Sex-Specific Toxicity and Physiological Responses to Thymol in a Common Bean Pest Acanthoscelides obtectus Say - Lazarević, Jelica; Jevremović, Stojan; Kostić, Igor; Vuleta, Ana; Manitašević Jovanović, Sanja; Kostić, Miroslav; Šešlija Jovanović, Darka (Frontiers in Physiology, 2022)
Acanthoscelides obtectus Say (Coleoptera: Chrysomelidae: Bruchinae), is one of the most important pests of the common bean Phaseolus vulgaris L. Without appropriate management it may cause significant seed loss in storages. In search for means of environmentally safe and effective protection of beans we assessed biological activity of thymol, an oxygenated monoterpene present in essential oils of many aromatic plants. We studied contact toxicity of thymol on bean seeds and its effects on adult longevity and emergence in F1 generation. Furthermore, we determined acetylcholinesterase (AChE), superoxide dismutase (SOD), catalase (CAT), mixed-function oxidase (MFO), carboxylesterases (CarE) and glutathione S-transferase (GST) activities in response to 24 h exposure of beetles to sublethal and lethal thymol concentrations. Our results showed that thymol decreased adult survival, longevity and percentage of adult emergence. Higher median lethal concentration (LC50) was recorded in females indicating their higher tolerance comparing to males. Overall, activities of SOD, CAT and CarE increased at sublethal and MFO increased at both sublethal and lethal thymol concentrations. On the other hand, GST and AChE activities decreased along with the increase in thymol concentrations from sublethal (1/5 of LC50, 1/2 of LC50) to lethal (LC50). Enzyme responses to the presence of thymol on bean seed were sex-specific. In the control group females had lower CarE and higher SOD, CAT and GST activity than males. In treatment groups, females had much higher CAT activity and much lower CarE activity than males. Our results contribute to deeper understanding of physiological mechanisms underlying thymol toxicity and tolerance which should be taken into account in future formulation of a thymol-based insecticide.